2017
DOI: 10.1002/lt.24672
|View full text |Cite
|
Sign up to set email alerts
|

The 24‐hour normothermic machine perfusion of discarded human liver grafts

Abstract: Donor organ shortage necessitates use of less than optimal donor allografts for transplantation. The current cold storage preservation technique fails to preserve marginal donor grafts sufficiently. Evidence from large animal experiments suggests superiority of normothermic machine preservation (NMP) of liver allografts. In this study, we analyze discarded human liver grafts that underwent NMP for the extended period of 24 hours. Thirteen human liver grafts which had been discarded for transplantation were ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 27 publications
1
78
0
Order By: Relevance
“…One liver exhibited continuous bile production and lactate clearance, but the lactate level after 6 hours of NMP remained higher than 3 mmol/L. Possibly, more prolonged time on NMP might have been useful, especially as recent reports have shown the feasibility of 24‐hour normothermic perfusion …”
Section: Discussionmentioning
confidence: 99%
“…One liver exhibited continuous bile production and lactate clearance, but the lactate level after 6 hours of NMP remained higher than 3 mmol/L. Possibly, more prolonged time on NMP might have been useful, especially as recent reports have shown the feasibility of 24‐hour normothermic perfusion …”
Section: Discussionmentioning
confidence: 99%
“…This setting challenges organ retrieval logistics, as the clinical reality usually includes organ retrieval and transplantation in different hospitals and sometimes even in different countries. In preclinical studies, preservation times were extended to 24 hours by normothermic PMP . However, an extension of cold ischaemic time (CIT) before commencement of MP significantly curtailed the protective effect of NMP in a porcine DCD model .…”
Section: Machine Perfusion–basic Principles and Mechanismsmentioning
confidence: 99%
“…49 Specifically, centers need to make timely decisions to allow reallocation of the organ to other centers based on current allocation policy. Research protocols using discarded human liver allografts have demonstrated that NMP can reliably perfuse livers for periods of up to 24 hours; however, efficient allocation mandates that perfusion should be limited to much shorter periods.…”
Section: How Long Should Accepting Centers Be Allowed To Perfuse Thmentioning
confidence: 99%